Prevalence and Predictors of Undiagnosed Hypertension in an Apparently Healthy Western Indian Population. (23rd February 2015) - Shukla, Anand N.; Madan, Tarun; Thakkar, Bhavesh M.; Parmar, Meena M.; Shah, Komal H.
Abstract : This epidemiological study was designed to evaluate the prevalence of undetected hypertension in an apparently healthy western Indian population having no history of major illness. 3629 individuals of≥ 18 years of age were included in the study. Hypertension (HTN) was defined as systolic blood pressure (SBP)≥ 140 mmHg or diastolic blood pressure (DBP) ≥ 90 mmHg and prehypertension (PHTN) as SBP ≥ 120–139 mmHg or DBP ≥ 80–89 mmHg, but without HTN. The prevalence of undiagnosed HTN in the total population was 26% and was 11% and 40% in the young (≤ 40-year) and old (> 40-year) populations, respectively. The prevalence of PHTN, 40% in the overall population, was nearly the same in the young (39%) and the old population (42%). The risk factor most strongly associated with PHTN and HTN was obesity, showing the highest odds ratio in the overall (PHTN 2.14; 95% CI 1.20–3.81; HTN 2.72; 95% CI 1.53–4.85), the young (PHTN 2.29; 95% CI 1.25–4.21; HTN 2.92; 95% CI 1.59–5.35), and the old (PHTN 1.13; 95% CI 0.65–1.96; HTN 1.38; 95% CI 0.79–2.4) populations. Hypertension is a major risk factor for cardiovascular diseases which must not be ignored, especially in the western Indian population.